2020
DOI: 10.3390/su12041407
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Swedish Diet Relative to Global and National Environmental Targets—Identification of Indicator Limitations and Data Gaps

Abstract: To reduce environmental burdens from the food system, a shift towards environmentally sustainable diets is needed. In this study, the environmental impacts of the Swedish diet were benchmarked relative to global environmental boundaries suggested by the EAT-Lancet Commission. To identify local environmental concerns not captured by the global boundaries, relationships between the global EAT-Lancet variables and the national Swedish Environmental Objectives (SEOs) were analysed and additional indicators for mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 45 publications
2
21
0
1
Order By: Relevance
“…In the present work, the GHG emissions from the diets varied from 1510 kg CO 2 eq per person per year (the Fast-Food diet) to 1830 kg CO 2 eq per person per year (the High-Beef diet). This range is similar to the results from other recently published work as regards Danish diets, (1590 kg CO 2 eq according to Bruno et al [ 20 ]), and Swedish diets (2 t CO 2 eq of which 11% were emissions from tropical deforestation according to Cederberg et al [ 80 ], and 2.2 t CO 2 eq from Moberg et al [ 101 ]). The estimates by Bruno et al [ 20 ] are based on supply data and a lower energy level (2000 kcal) of the diet than the present study and, like the present study, do not include GHG emissions related to land use changes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present work, the GHG emissions from the diets varied from 1510 kg CO 2 eq per person per year (the Fast-Food diet) to 1830 kg CO 2 eq per person per year (the High-Beef diet). This range is similar to the results from other recently published work as regards Danish diets, (1590 kg CO 2 eq according to Bruno et al [ 20 ]), and Swedish diets (2 t CO 2 eq of which 11% were emissions from tropical deforestation according to Cederberg et al [ 80 ], and 2.2 t CO 2 eq from Moberg et al [ 101 ]). The estimates by Bruno et al [ 20 ] are based on supply data and a lower energy level (2000 kcal) of the diet than the present study and, like the present study, do not include GHG emissions related to land use changes.…”
Section: Discussionsupporting
confidence: 91%
“…The relatively high intake per day gives this substantial contribution to the GHG emission of the diet. Saxe et al [ 104 ] and Moberg et al [ 101 ] found similar GHG emissions caused by the consumption of sweets, snacks and drinks (excluding milk), and also Kanemoto et al [ 105 ] showed that consumption of confectionary and alcohol contributes significantly to climate change. At the same time, a high intake of soft drinks, sweets and alcohol is negatively associated to health [ 106 , 107 , 108 , 109 ] and both NNR2012 [ 76 ] and WHO recommend to limit the intake hereof [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though chicken meat contributes to fewer GHG emissions than other types of meat, the contribution is still substantially higher compared with plant-based protein sources [ 34 ]. Moberg et al [ 5 ] stated that animal products are responsible for more than half (about 67%) of the climate impact caused by the average diet in Sweden. Therefore, it would be preferable for both public health and the environment to change the consumption to more plant-based protein.…”
Section: Discussionmentioning
confidence: 99%
“…Despite awareness of sustainable development challenges, the average Swedish diet also exceeds the global planetary boundaries for GHG emissions [ 3 ]. A shift toward environmentally sustainable diets is needed [ 5 ]. Swedish residents are consuming too much added sugar, saturated fat and sodium, and not enough fruit, vegetables, wholegrains or fibers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 4 In order not to jeopardise the sustainability of Earth system processes, the EAT-Lancet Commission proposed six absolute planetary boundaries within which food production should operate: global scale targets for greenhouse gas emissions, nitrogen and phosphorus cycling, freshwater use, biodiversity loss, and land-system use (Willett et al, 2019). Limitations of these environmental indicators include an inability to capture all issues and the risks of overlooking crucial or underestimating known factors when applied at the global, regional, national, and/or local level; see, for example, Schuftan et al (2014), Taylor (2018), Carrasco-Torrontegui et al (2020), Hanieh et al (2020), Kennedy et al (2020), and Moberg et al (2020). Adopting a whole supply chain/ network perspective on the food system takes into account myriad actors and their spatiotemporal relationships: from farm-to-fork, an understanding of which people/interactions are measured and who/what is missing.…”
Section: Introductionmentioning
confidence: 99%